Resiliensi Muallaf Laki-Laki Ditinjau dari Aspek Mental dan Spiritual - Aziz, Abdul; Lestari, Chika (Department of Islamic Guidance and Counseling, 2023)
This study aims to find out how the efforts of male converts to defend their Islam are viewed from a mental and spiritual aspect, looking at mental and spiritual conditions during the transformation from the old religion to Islam and after. In writing this research, the researcher used a qualitative descriptive method supported by resilience theory. By looking at male converts as the subject of this study and the interviews in this study. Some important things that concern the researchers are how the mental condition of converts in carrying out their daily activities after becoming converts, the motivation to become a convert and the efforts made to defend themselves amid pressure and the influence of Islamic spirituality on the mental condition of converts, what are the challenges while becoming a Muslim convert? convert. Based on the results of the study that the subject has good resilience. In this study, it can be concluded that aspects of resilience such as managing emotions in certain situations and conditions, then the subject can control the situation and have good Self-Efficacy in overcoming problems so that he is able to rise and achieve his desires well